Psychometric accuracy of the Dutch Child and Adolescent Trauma Screener - Lieke H. Kooij; Irma M. Hein; Cedric Sachser; Samantha Bouwmeester; Madelief Bosse; Ramón J. L. Lindauer (European Journal of Psychotraumatology)
Objective: The aim of this study is to investigate the psychometrics of the Dutch version of the Child and Adolescent Trauma Screener (CATS-2). By this, an international recognized instrument to screen symptoms of post-traumatic stress (PTSS) in children and adolescents according to the Diagnostic and Statistical Manual for Mental Disorders, 5th edition (DSM-5) becomes available for Dutch youth.Procedure and Method: Based on the validated CATS-2 we established the Dutch version, named the KJTS. A total of 587 children and adolescent, age 7–21, and 658 caregivers referred to mental health care services in Amsterdam was included in the study to examine psychometric properties. The construct was tested by confirmatory factor analysis (CFA). Furthermore reliability, convergent-divergent patterns and diagnostic test accuracy were examined.Results: The underlying DSM-5 factor structure with four symptom clusters (re-experiencing, avoidance, negative alterations in mood and cognitions, hyperarousal) was supported by CFA showing a good fit for the selfreport (CFI = .95, TLI = .94), and an acceptable fit for the caregiver report (CFI = .90, TLI = .89). The KJTS showed excellent reliability (alpha = .92) on both selfreport and caregiver report. The convergent-discriminant validity pattern showed medium to strong correlations with measures of internalization problems, such as anxiety and affective problems (r = .44–.72) and low to medium correlations with externalizing symptoms (r = .21–.36). The ROC-curve analysis has proven a good accuracy (AUC = .81; n = 106).Discussion and conclusion: This study demonstrates the psychometric accuracy of the KJTS in a Dutch clinical population. The KJTS reflects adequately the dimensionality of PTSD as described in the DSM-5, with a good fit for selfreports, an acceptable fit for caregiver reports, excellent reliability and sufficient validity. Limitations are described. The outcomes support the use of the KJTS in research and clinical practice for screening and monitoring of PTSS.